How digitalized are school students? Determining digital competencies and motivation factors in using technology for learning - Omar, Muhd Khaizer; Ahmad Ruzaidi, Dalia Umaira; Mohd Puad, Mohd Hazwan; Jusoh, Rosnani (Human Resource Management Academic Research Society, 2023)
Technology in education has placed a great necessity in our education system. The teaching and learning process demonstrates more technology optimization due to the uncertain ecosystem that is happening around the globe. New modalities are being introduced as pedagogical supports to enrich students’ learning experiences. However, a few issues arose related to motivation and adaptation to digitalization in the learning milieu among young learners. For instance, educators lack competency in utilizing specific technology and less motivation to engage students optimizing specific digital applications supporting their learning in the most effective ways. This research determines the relationship between digital competency and the motivation of secondary school students in the Klang Valley area. A quantitative correlation study design was employed involving 260 students who enrolled in Design and Technology (D&T) subjects from four public secondary schools. A self-developed questionnaire was validated by experts and piloted as instrumentation. The data of this research study was further analyzed using Statistical Package for Social Sciences (SPSS) version 27 software involving descriptive and inferential analysis. The findings were discussed and it is hoped the findings of the study would enlighten the educational stakeholders to spearhead the digitalization effort in the nation.